Ցեղասպանության իրագործման արդի սպառնալիքները - Պողոսյան, Նարեկ Մ. (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
The article discusses the persistent and evolving threat of genocide throughout history and into modern times. Despite significant human progress, the danger of targeting ethnic, religious, and racial groups remains, with new threats emerging. Among the contemporary threats to the realization of genocide, the article considers the exacerbation of ethnic and religious conflicts, political instability, disinformation and propaganda to influence public perceptions, dehumanization and hate speech, the emergence and spread of extremist ideologies, climate, environmental change and the issue of resource scarcity, forced displacements and refugee crises, economic inequality and marginalization, the proliferation of arms and militarization of society, development of biotechnology, use of artificial intelligence, cyber-attacks, and information manipulation. Additionally, the lack of rule of law, impunity, and the devaluation and denial of the concept of genocide create new threats. The article emphasizes the importance of a proactive international agenda for the prevention of genocide and other crimes, highlighting the crucial role of individual UN member states. Armenia’s active engagement in presenting resolutions on genocide prevention within the UN framework is cited as a significant example of such proactiveness. В статье рассматривается постоянная и развивающаяся угроза геноцида на протяжении истории и в современных условиях. Несмотря на значительный прогресс человечества, опасность уничтожения этнических, религиозных и расовых групп остается, и появляются новые угрозы. Среди современных угроз реализации геноцида в статье рассматриваются обострение этнических и религиозных конфликтов, политическая нестабильность, дезинформация и пропаганда для влияния на общественное мнение, дегуманизация и язык вражды, возникновение и распространение экстремистских идеологий, изменение климата и проблема дефицита ресурсов, вынужденные переселения и кризисы беженцев, экономическое неравенство и маргинализация, распространение оружия и милитари- зация общества, развитие биотехнологий, использование искусственного интеллекта, кибератаки и манипуляция информацией. Кроме того, отсутствие верховенства закона, безнаказанность, девальвация и отрицание концепции геноцида создают новые угрозы. В статье подчеркивается важность проактивной международной повестки для предотвращения геноцида и других преступлений, отмечая решающую роль отдельных государств-членов ООН. Активное участие Армении в представлении резолюций по предотвращению геноцида в рамках ООН приводится как значительный пример такой проактивности.
Keywords: Ցեղասպանություն